Kentucky hauntings : homespun ghost stories and unexplained history - Brown, Roberta Simpson, 1939- (University Press of Kentucky, 2013)
More than evoking chills down the spine and cautious glances over one's shoulder, spooky stories create lasting bonds and memories between friends and family. The tradition of storytelling ties generations together with exciting new tales and familiar folklore that has sparked superstitions and legends. In this book, two storytellers present a collection of paranormal tales that will appeal to anyone looking for a friendly scare.